Photonic nanostructures for advanced light trapping in silicon solar cells: the impact of etching on the material electronic quality. Issue 2 (24th November 2015) - Trompoukis, Christos; Stesmans, Andre; Simoen, Eddy; Depauw, Valérie; El Daif, Ounsi; Lee, Kidong; Gordon, Ivan; Mertens, Robert; Poortmans, Jef
Abstract : Dry plasma etching, commonly used by the Photonics community as the etching technique for the fabrication of photonic nanostructures, could be a source of device performance limitations when used in the frame of silicon photovoltaics. So far, the lack of silicon solar cells with state‐of‐the‐art efficiencies utilizing nanophotonic concepts shows how challenging their integration is, owing to the trade‐off between optical and electrical properties. In this study we show that dry plasma etching results in the degradation of the silicon material quality due to (i) a high density of dangling bonds and (ii) the presence of sub‐surface defects, resulting in high surface recombination velocities and low minority carrier lifetimes. On the contrary, wet chemical anisotropic etching used as an alternative, leads to the formation of inverted nanopyramids that result in low surface recombination velocity and low density of dangling bonds. The proposed inverted nanopyramids could enable high efficiency photonic assisted solar cells by offering the potential to achieve higher short‐circuit current without degrading the open circuit voltage. (© 2016 WILEY‐VCH Verlag GmbH &Co. KGaA, Weinheim) Abstract : In this study the authors show that dry plasma etching, used in the frame of photonic‐assisted light trapping for crystalline silicon photovoltaics, results in low minority carrier lifetimes due to a high density of dangling bonds and the presence of sub‐surface defects. On the contrary, inverted nanopyramids formed by wet chemical anisotropic etching enables high minority carrier lifetimes, offering the potential to achieve high open‐circuit voltage values.